PROFIL VERTIKAL DAN HORIZONTAL PARAMETER SALINITAS, DHL, DAN TDS BERDASARKAN VARIASI MUSIMAN DI ESTUARI SUNGAI CITARUM - Nurul Fahimah; Annisa Dwi Damayanti; Venny Ulya Bunga; Haryo Mubiarto (OSEANA, 2021)
Salinity, electrical conductivity (EC), and Total Dissolved Solid (TDS) are parameters that pose an important role in the distributions of environmental pollution substances in the estuary. The difference in salinity, EC, and TDS concentration vertically (based on the depth in the water column) and horizontally (based on the distance from the estuary mouth) will affect the process of pollutant’s transportation and transformation in the estuary. On the other hand, seasonal variations will also affect parameters. Therefore, the information related to the vertical and horizontal profiles of salinity and other parameters based on seasonal variations is necessary to study. The purpose of this study is to analyze the vertical profile and horizontal-vertical of salinity, EC, and TDS concentrations during the rainy season and dry season in the estuary of Citarum River. This research was conducted in April 2018 (rainy season) and August 2018 (dry season) when the low tide. The measurement of salinity, EC, and TDS was directly conducted in the field using a conductivity meter. The results show that the concentration level of salinity, EC, and TDS showed a vertical and horizontal difference in the estuary of the Citarum River. In addition, there are differences in the concentration of salinity, electrical conductivity, TDS in the rainy season and dry season in the estuary of the Citarum River. The level of TDS has a linear relationship between salinity and electrical conductivity, with a value of R2 >95%.